Treat or treatment : a qualitative study analyzing patients' use of complementary and alternative medicine - Bishop, Felicity L. (2008)
Analyses how patients use complementary and alternative medicine (CAM) and examines how patients' perspectives relate to existing, expert-led taxonomies.